2007
DOI: 10.1002/cncr.22822
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel: A therapeutic option in the treatment of cutaneous angiosarcoma

Abstract: BACKGROUND.Effective treatment options are limited for patients with cutaneous angiosarcoma (AS). Docetaxel, a member of the taxane family of drugs, reportedly has been effective in the treatment of lung, head and neck, and breast cancers. Another taxane drug, paclitaxel, reportedly had unique activity in the treatment of AS of the scalp and neck and acquired immunodeficiency syndrome‐related Kaposi sarcoma. Therefore, the authors hypothesized that docetaxel may be of value in the treatment of cutaneous AS tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 16 publications
(24 reference statements)
0
80
0
Order By: Relevance
“…A meta-analysis of localised soft tissue sarcomas of adults has provided evidence that adjuvant doxorubicin-based chemotherapy is useful in this regard as it significantly improved the distant recurrence-free time [11]. Recently, several reports have indicated that, owing to its angiogenic activity, taxane-based chemotherapy offers clinical benefit to patients with angiosarcoma [8,12]. Isogai et al [12] reported that docetaxel treatment of a patient with angiosarcoma of the scalp with lung metastases resulted in complete remission of lung metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of localised soft tissue sarcomas of adults has provided evidence that adjuvant doxorubicin-based chemotherapy is useful in this regard as it significantly improved the distant recurrence-free time [11]. Recently, several reports have indicated that, owing to its angiogenic activity, taxane-based chemotherapy offers clinical benefit to patients with angiosarcoma [8,12]. Isogai et al [12] reported that docetaxel treatment of a patient with angiosarcoma of the scalp with lung metastases resulted in complete remission of lung metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several authors advocated a combination of surgery and radiotherapy for these tumours [3,6,7]. Recently, chemotherapy and immunotherapy using recombinant interleukin-2 (rIL-2) have been studied as potential treatments [8,9]. However, the optimal treatment for these tumours has not been clearly established.…”
mentioning
confidence: 99%
“…For metastatic angiosarcomas, chemotherapy is the primary choice of treatment 9) . Agents reported to be effective against angiosarcoma are PTX 10,11) , DOC 12,13) , gemcitabine 14) , bevacizumab 15) , and sorafenib 16) . However, it is difficult to prevent the disease from progressing to metastatic angiosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Isogai et al [25] anti angiogenic effect [26][27][28]. In the Fata et al [27], a response rate of 89% by paclitaxel for angiosarcoma of the scalp or face was noted.…”
Section: Commentariesmentioning
confidence: 99%